2018
DOI: 10.1021/acs.cgd.8b01369
|View full text |Cite
|
Sign up to set email alerts
|

Disclosing the Properties of a New Ce(III)-Based MOF: Ce2(NDC)3(DMF)2

Abstract: The new Ce(III) based metal-organic framework Ce 2 (NDC) 3 (DMF) 2 , containing the simple ditopic linker napthalenedicarboxylate (NDC 2-), has been synthesized under solvothermal reaction conditions with high purity and yield. Its crystal structure was determined with SC-XRD techniques and further confirmed by Ce K-edge XAS. Upon thermal activation the compound revealed a phase transformation at about 300°C involving the removal of the solvent molecules which has been investigated in detail by TGA, VT-PXRD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Ce-based MOFs have recently created interest in the scientific community. General features that can be drawn from looking at the current published literature are the following: (i) both Ce 3+ and Ce 4+ oxidation states can be used in the synthesis of MOFs [5][6][7][8][9]; (ii) synthetic conditions for Ce 3+ -containing MOFs tends to be harsher than Ce 4+ [5,6,10]; (iii) usually, Ce 4+ starting reagents may be reduced to Ce 3+ during the synthesis [11,12]; (iv) Ce 3+ materials more frequently have peculiar structures, while Ce 4+ tends to give rise to MOFs with the same structure as other 4+ cations (e.g., Zr 4+ or Hf 4+ ) [5][6][7]13,14]. Their thermal stability is generally lower than their Zr 4+ counterparts [7,8,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ce-based MOFs have recently created interest in the scientific community. General features that can be drawn from looking at the current published literature are the following: (i) both Ce 3+ and Ce 4+ oxidation states can be used in the synthesis of MOFs [5][6][7][8][9]; (ii) synthetic conditions for Ce 3+ -containing MOFs tends to be harsher than Ce 4+ [5,6,10]; (iii) usually, Ce 4+ starting reagents may be reduced to Ce 3+ during the synthesis [11,12]; (iv) Ce 3+ materials more frequently have peculiar structures, while Ce 4+ tends to give rise to MOFs with the same structure as other 4+ cations (e.g., Zr 4+ or Hf 4+ ) [5][6][7]13,14]. Their thermal stability is generally lower than their Zr 4+ counterparts [7,8,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Their thermal stability is generally lower than their Zr 4+ counterparts [7,8,14,15]. As a possible application of Ce MOFs as redox catalysts, Smolders et al [8] reported the successful use of Ce 4+ -UiO-67 in the aerobic oxidation of benzylic alcohol to benzaldehyde mediated by TEMPO (2,2,6,. Furthermore, Ethiraj et al [5] reported the use of a Ce 3+ -based MOF for the selective capture and storage of CO 2 , obtaining high figures of merit of capacity and separation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the ability to remove solvent molecules from the materials, none were found to be porous to N 2 at 77 K. Removal of coordinated DMF from 1 and 4 presumably results in framework collapse, although it is noted that during the peer review period, a Ce(III) analog of 1 was reported which could be desolvated at 300°C to a phase that was porous to CO 2 (Atzori et al, in press). For 5 , whilst the framework does show void space, it is possible that access to the void channels is blocked due to charge-balancing dimethylammonium ions lying in the cluster layer of the framework.…”
Section: Resultsmentioning
confidence: 99%
“…90 A highly selective adsorption of CO 2 has been reported for the green CD-MOF-2 formed by the renewable cyclic oligosaccharide γ-cyclodextrin and RbOH, the reversible carbon fixation occurring through carbonate formation and decomposition at room temperature. 91…”
Section: Carboxylatesmentioning
confidence: 99%